Significance of the Regional Human Rights Mechanisms: Interactions Between the Inter-American and European System of Human Rights - Czepek, Jakub J. (Regional Human Rights Protection Systems Outside Europe, 2026)
Over the years, the American and European system of human rights protection have developed their legal ecosystems, which address human rights violations. However, both systems differ based on numerous factors, including legal traditions, legal systems, culture, human rights challenges, resources and other particularities of the region. Nonetheless, both systems share certain similarities as well. They are both based on fundamental values enshrined in the Universal Declaration of Human Rights (UDHR) and initially shared the same institutional blueprint, which was procedurally visible before the adoption of Additional Protocol No. 11 to the European Convention of Human Rights (ECHR). Even though the approach to certain rights and their interpretation by both European and Inter-American Courts may differ, both systems interact and influence each other. This relation is visible in the jurisprudence of both Courts. Both approach certain rights or freedoms similarly and refer to each other’s case laws. This chapter compares both systems and examines their mutual influences.Keywords: Inter-American Court of Human rights, European Court of Human Rights, ECHR, ACHR, case law, regional human rights systems, Inter-American human rights protection system